2017
DOI: 10.1186/s13053-016-0061-6
|View full text |Cite
|
Sign up to set email alerts
|

How does genetic risk information for Lynch syndrome translate to risk management behaviours?

Abstract: BackgroundThere is limited research on why some individuals who have undergone predictive genetic testing for Lynch syndrome do not adhere to screening recommendations. This study aimed to explore qualitatively how Lynch syndrome non-carriers and carriers translate genetic risk information and advice to decisions about risk managment behaviours in the Australian healthcare system.MethodsParticipants of the Australasian Colorectal Cancer Family Registry who had undergone predictive genetic testing for Lynch syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
(38 reference statements)
1
10
0
Order By: Relevance
“…All P/LPVs identified in our study are heterozygous variants. This is in accordance with the mode of inheritance for these genes regarding their association with pancreatic cancer susceptibility [ 29 ].…”
Section: Discussionsupporting
confidence: 85%
“…All P/LPVs identified in our study are heterozygous variants. This is in accordance with the mode of inheritance for these genes regarding their association with pancreatic cancer susceptibility [ 29 ].…”
Section: Discussionsupporting
confidence: 85%
“…Finally, we observed that BRAF was the most common gene mutated among samples, in agreement with previous studies, where BRAF mutations were very frequent in SSA (75%) and in mixed polyps (86%) [ 42 ]. Accordingly, Horpaopan et al [ 43 ] detected that 50% of serrated polyps presented BRAF p.V600E mutation in a 41-years old female patient.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of both genetic and environmental factors contributes to CRC formation. It is estimated that > 35% of CRC development is due to genetic predisposition, wherein nearly 1% of all CRCs are attributed to familial adenomatous polyposis (FAP) ( 87 , 88 ). FAP is an autosomal dominant inherited disorder that describes the development of numerous colorectal adenomatous polyps.…”
Section: Literature Reviewmentioning
confidence: 99%